HOSTAGE OF HER OWN TALENT: THE TRAGIC PATH TO RECOGNITION OF HANNA SOBACHKO - Zhadeiko, Olexiy (Theory and practice of design, 2025)
The purpose of this investigation is to actualize the creative work of Hanna Sobachko-Shostak in the context of the realities of modern artistic processes, an attempt to rethink the creative heritage of the artist in the context of military events that provoke a change in the prism of consideration. Methodology. To fulfill the tasks set in the article, the tools of complex, chronological, historical, biographical, comparative methods are used, which makes it possible to look broadly at the analyzed phenomenon and analyze it at the junction of different branches of knowledge – aesthetics, cultural studies, art history, since it has a generally significant character and lies at the intersection of several scientific fields. Results. The artist from a small Ukrainian village, even today, sixty years after her death, is an imperfectly illuminated phenomenon of national culture, which requires not only a more detailed study, but also a rethinking, first of all, of the role of her heritage in the context of today’s challenges. The influence of the artist’s creativity on her artistic environment, the potential of her art works for many spheres of artistic life, including modern life, is emphasized. The tragic fate of the artist, who was dependent all her life on a number of factors that did not allow her talent to reveal itself in full force, is emphasized, and in the last years of her life her works were created far beyond the borders of the Motherland, which was the source of inspiration for her image-making. The dissonance between the nature of the purely national content of the artist’s creative manner and the conditions in which she created a significant part of her life, far beyond the borders of Ukraine, is highlighted. The scientific novelty of the stated maxims is seen primarily in a different, relevant in the light of modern realities, point of view, which is proposed for rethinking the role, the significance of the creative legacy of Hanna Sobachko-Shostak for modern Ukrainians. This gives prospects for further scientific research. Tasks for future explorations in this area are outlined. The practical relevance of the research is embodied primarily in the great potential of the material if it is implemented in special courses not only for future art historians, but also as a segment of the education of designers, textile specialists, ceramics, and decorators, as well as a basis for large-scale interdisciplinary exhibition projects.